Treatment of severe hemolysis following Nit-Occlud Lê VSD coil implantation with Amplatzer Duct Occluder II - Mustafa Orhan Bulut; Mehmet Küçük; Şevket Ballı; Ahmet Çelebi (KARE Publishing, 2016)
Hemolysis after percutaneous device closure of ventricular septal defect (VSD) is a rare complication that can be conservatively managed in the majority of cases. However, surgery or transcatheter occlusion may be necessary. Presently described is the successful treatment of hemolysis that developed after implantation of the Nit-Occlud Lê VSD coil, using the Amplatzer Duct Occluder II (ADO II) in a patient with aneurysmatic perimembranous VSD. Systolic murmur and symptoms immediately disappeared after the procedure.